2008
DOI: 10.1063/1.2889945
|View full text |Cite
|
Sign up to set email alerts
|

Test of the consistency of various linearized semiclassical initial value time correlation functions in application to inelastic neutron scattering from liquid para-hydrogen

Abstract: The linearized approximation to the semiclassical initial value representation (LSC-IVR) is used to calculate time correlation functions relevant to the incoherent dynamic structure factor for inelastic neutron scattering from liquid para-hydrogen at 14 K. Various time correlations functions were used which, if evaluated exactly, would give identical results, but they do not because the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 129 publications
(122 reference statements)
0
49
0
Order By: Relevance
“…The degree to which this affects the accuracy of the LSC-IVR in practical applications is subtle, since the LSC-IVR quantizes  β rather than the Boltzmann density operator . A previous investigation 26 suggested that this inconsistency in the LSC-IVR correlation function may be most noticeable at very long time for some systems at quite low temperature.…”
Section: Linearized Semi-classical Initial Value Representation (Lmentioning
confidence: 99%
See 4 more Smart Citations
“…The degree to which this affects the accuracy of the LSC-IVR in practical applications is subtle, since the LSC-IVR quantizes  β rather than the Boltzmann density operator . A previous investigation 26 suggested that this inconsistency in the LSC-IVR correlation function may be most noticeable at very long time for some systems at quite low temperature.…”
Section: Linearized Semi-classical Initial Value Representation (Lmentioning
confidence: 99%
“…There are other ways to derive the classical Wigner model (or one may simply postulate it) 6,44,49,50 , and we also note that the 'forward-backward semiclassical dynamics' (FBSD) approximation of Makri et al 24,[28][29][30][51][52][53][54][55][56][57][58][59][60][61][62] is very similar to it. The LSC-IVR/classical Wigner model cannot describe true quantum coherence effects in time correlation functions-more accurate SC-IVR approaches, such as the Fourier transform forward-backward IVR (FB-IVR) approach 22,63 , or the still more accurate generalized FB-IVR 64 and exact FB-IVR 5 of Miller et al , are needed for this-but it does describe some aspects of the quantum dynamics very well [24][25][26][34][35][36][37][38]41,42,[65][66][67] . E.g., the LSC-IVR has been shown to describe the strong tunneling regime 42 in reactive flux auto-correlation functions (which determine chemical reaction rates) quite well, and also velocity autocorrelation functions 24,25,66,67 , force autocorrelation functions 25,[34][35]...…”
Section: ˆ/ Iht E −mentioning
confidence: 99%
See 3 more Smart Citations